First and second law analysis of a gasoline engine for various compression ratios. (16th April 2009) - Parlak, Adnan; Erbas, Yavuz; Yasar, Halit; Soyhan, Hakan; , Cengiz Deniz
This article presents a comparative energy and exergy analyses of a single cylinder, four-stroke spark-ignition engine for three compression ratios. A Petter engine with variable compression ratio and ignition timing was used to obtain the experimental data at full load conditions for six engine speeds between 1, 300 and 2, 800 rpm. It was found that the first and the second law efficiencies increased with increasing compression ratio. The maximum extractable power was obtained at the compression ratio 6.2 and observed inversely proportional to the compression ratio.